2012
DOI: 10.1111/j.1365-2095.2011.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance, body compositions, input and output of nitrogen and phosphorus in Siberian sturgeon, Acipenser baerii Brandt, as affected by dietary animal protein blend replacing fishmeal and protein levels

Abstract: An 8-week growth trial was conducted using a 2 · 3 factorial design to evaluate the effect of substitution of fishmeal (FM) by rendered animal protein blend [APB, comprised of 400 g kg )1 poultry by-product meal, 350 g kg )1 meat and bone meal, 200 g kg )1 hydrolysed feather meal (HFM) and 50 g kg )1 spray-dried blood meal] in diets of Siberian sturgeon, Acipenser baerii Brandt. Two isoenergetic control diets were formulated to contain two different protein levels [highprotein control (400 g kg )1 ), with 483 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
4
31
0
1
Order By: Relevance
“…However, Xue et al . () recently reported that total FM protein replaced by animal protein blend did not show significant negative effect on growth of Siberian sturgeon when dietary Lys, Met and Thr were balanced by CAAs. In the present study, regardless of protein levels, SGRs of fish fed the PPB‐based diets supplemented with CAAs and MCP were similar to those of fish fed FM‐based diets.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, Xue et al . () recently reported that total FM protein replaced by animal protein blend did not show significant negative effect on growth of Siberian sturgeon when dietary Lys, Met and Thr were balanced by CAAs. In the present study, regardless of protein levels, SGRs of fish fed the PPB‐based diets supplemented with CAAs and MCP were similar to those of fish fed FM‐based diets.…”
Section: Discussionmentioning
confidence: 92%
“…; Xue et al . ). Similar results have been shown in other fish species, such as turbot ( Psetta maxima ; Fournier et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was characterized by high protein content, favorable amino acid profile, no anti-nutritional factor, and reasonable palatability. Studies (Rawles et al, 2006;Saadiah et al, 2011;Zhou et al, 2011;Xue et al, 2012) of PPBM showed that high quality PPBM is rich in protein and low in ash, which may lead to the good palatable effect. On the other hand, studies (Francis et al, 2001;Hasimoglu et al, 2007) of SBM have indicated that antinutritional factors, such as trypsin inhibitor, polysaccharides, tannin, saponin and phytic acid, may affect its palatability to turbot.…”
Section: Discussionmentioning
confidence: 98%